Identification of material sustainability matters in the property development industry by analysing stakeholder perspectives on ten sustainable elements - Wei Yee, Moo (2025)
Despite the global emphasis on sustainability, property developers in Malaysia face significant challenges in implementing sustainable practices due to the multifaceted consideration of the risk of incremental cost, instability of advanced technology, lack of skilled experts, and shortage of green materials. The author of this paper aims to address the gap in understanding the perceived value of sustainable practices among various stakeholders, which may not align with the principles of the sustainability frameworks.